Correlation between Positive Rate and Number of Biopsy Samples on Urease Test in Childhood Helicobacter pylori Infection - Seo, Ji-Hyun; Park, Ji Sook; Yeom, Jung Sook; Lim, Jae-Young; Park, Chan-Hoo; Woo, Hyang-Ok; Baik, Seung-Chul; Lee, Woo-Kon; Cho, Myung-Je; Rhee, Kwang-Ho; Youn, Hee-Shang (Journal of Korean medical science, 2014)
To identify the correlation between the number of gastric biopsy samples and the positive rate, we compared the results of urease test using one and three biopsy samples from each 255 children who underwent gastroduodenoscopy at Gyeongsang National University Hospital. The children were divided into three age groups: 0-4, 5-9, and 10-15 yr. The gastric endoscopic biopsies were subjected to the urease test. That is, one and three gastric antral biopsy samples were collected from the same child. The results of urease test were classified into three grades: Grade 0 (no change), 1 (6-24 hr), 2 (1-6 hr), and 3 (<1 hr). The positive rate of urease test was increased by the age with no respect to the number of gastric biopsy samples (one biopsy P = 0.001, three biopsy P < 0.001). The positive rate of the urease test was higher on three biopsy samples as compared with one biopsy sample (P < 0.001). The difference between one and three biopsy samples was higher in the children aged 0-9 yr. Our results indicate that the urease test might be a more accurate diagnostic modality when it is performed on three or more biopsy samples in children.